Climate Shocks and Sino-nomadic Conflict - Bai, Ying; Kung, James Kai-sing (The Review of Economics and Statistics, 2011)
Employing droughts and floods to proxy for changes in precipitation, this paper shows nomadic incursions into settled Han Chinese regions over a period of more than two thousand years—the most enduring clash of civilizations in history—to be positively correlated with less rainfall and negatively correlated with more rainfall. Consistent with findings that economic shocks are positively correlated with conflicts in modern sub-Saharan Africa when instrumented by rainfall, our reduced-form results extend this relationship to a very different temporal and geographical context, the Asian continent, and long historical period.